Evaluasi Program Penanggulangan Gelandangan Dan Pengemis (GEPENG) di Kabupaten Demak - Nindya Khasna A.; Tri Yuniningsih; Ida Hayu D. (Journal of Public Policy and Management Review)
This study examines the problems of the homeless and beggars in the Kabupaten Demak. The emergence of homeless and beggars is the accumulation and interaction of variety problems such as poverty, lack of skills work of which is owned, low education, environment, social, cultural, healthty. Therefore the problem of homeless and beggars should be treated immediately so as not to bring up other issues such as: environmental problems, population problems, as well as the issue of security, order, and crime. While the failure of efforts to control the vagabonds and beggars can be caused due to lack of resources, Lack of capacity 2 and capabilities of the committee, the socialization, the monitoring that does not go well, the mismatch between planning with the implementation of the program. This study uses a qualitative descriptive approach. To see the implementation of the program is running, the researcher used the theory of Korten, namely the suitability of between 3 elements: programs, organizations, and benefits. The stage of the evaluation the researcher used the theory of Dunn, namely effectiveness, efficiency, adequacy, alignment, responsifitas, and accuracy. The results showed that reduction programs homeless and beggars that are being implemented this has not been successful due to the lack of compatibility between the program with the implementing organization, the traffic that is owned implementing units, as well the last of the benefits the program have not been fully felt by the beneficiaries.